Youths' Perception of Digital Security Act 2018: A Study on the Youth of Bangladesh - Etee, Nowshin Jahan; Mukta, Jakia Jahan (South Asian Journal of Social Sciences and Humanities, 2022)
Freedom of speech is one of the most important fundamental rights ensured by the constitution  of the People's Republic of Bangladesh. However, when this right is abused, it destroys the peace  and harmony of the country. But without any surveillance, digital platforms can turn into places  of controversy which may trigger mass people into communal violence and riots. Thus, the  government of Bangladesh has introduced Digital Security Act 2018 to secure the responsible  use of the Internet and digital platforms. In this study, the researchers attempted to take a look at  the perception of Bangladeshi youth on the Digital Security Act 2018. This study followed  survey and in-depth interview methods to gather data. Researchers found out that most young  people feel the digital security act is working against freedom of expression on social media.  They demand viable changes to this act and agreed to the notion that responsible digital  citizenship can ensure freedom of expression on social media.
Keywords: Youth; Perception; Digital; Security